New anatomical insights into preventing brow ptosis with botulinum toxin-A use (Canadian Dermatology Today, 2021)
Botulinum toxin-A (BTX-A) injections were the most commonly performed  non-surgical procedure in 2020 according to the Aesthetic Plastic Surgery National Databank Statistics. Between 2019 and 2020, the number of neurotoxin injections performed in the United States has risen 1.5 fold from 1,712,994 to 2,643,366. When utilizing BTX-A in the upper face, the incidence of eyebrow ptosis varies widely and has been quoted in the literature at upwards of 20%. This adverse event is not exclusively seen post-treatment of the frontalis muscle but can also occur through inadvertent diffusion of the neurotoxin when treating the glabellar complex. Over the past year, new anatomic considerations to help injectors optimize results and reduce the risk of eyebrow ptosis with frontalis and glabellar BTX-A injections have been published. This paper aims to summarize three such publications which may help to positively impact injectable outcomes in the clinician’s day-to-day practice.